Four-membered heterocyclic molecules featuring boron and heavy group 14 elements that exhibit both σ-aromatic and π-aromatic properties: a new synthetic target - Zhang, Zheng-Feng (2024)
In this study, we present a series of theoretically designed B2G14G14' molecules, featuring four-membered-ring heterocycles containing boron and heavy group 14 elements (G14 and G14' = Si, Ge, Sn, and Pb). Through the use of density functional theory (DFT), natural bond orbital (NBO) analysis, quantum theory of atoms in molecules (QTAIM), and electron localization function (ELF), our studies demonstrate a strong π single bond between the bridgehead G14 and G14' atoms, with minimal participation from a very weak G14-G14' σ bond. Additionally, the nucleus independent chemical shift (NICS), anisotropy of current-induced density (ACID), and adaptive natural density partitioning (AdNDP) analyses definitively establish the presence of both σ-aromaticity and π-aromaticity in these inorganic four-membered heterocyclic neutral molecules.